ANTIDIABETIC ACTIVITY TEST OF ETHANOL EXTRACT BROCOLI (BRASSICA OLERACEA VAR. ITALICA) IN WHITE MALE RATS - Purba, Novandi; Handayani, Diah Tri; Cahayani Zebua, Kristian; Harefa, Karnirius (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Diabetes is a chronic disease characterized by excessive blood glucose levels caused by absolute and relative insulin deficiency. The stages in this study were sampling, identification of samples/plants, simplification, simplification screening, and preparation of extracts by maceration. The method used in the diabetes activity test uses a glucometer to induce alloxan in rats at a dose of 150 mg/kg body weight. The test animals were 25 rats which were divided into 5 treatment groups namely CMC Na 0.5% (negative control), glibenclamide (positive control) 0.45 mg/kg body weight and EEB dose 200 mg/kg body weight, 400 mg/kg body weight and 600. mg/kg body weight. kg B.W. kg body weight as a test material given orally. Measurement of blood glucose values ??according to Allox and on days 3, 5, and 7 after administration of the test substance, namely EEB. The test results data were analyzed statistically using one-way ANOVA at a 95% confidence level followed by Tukey's post hoc test. The results of the phytochemical screening showed that EEB contains alkaloids, flavonoids, tannins, saponins, and glycosides. The results of the diabetes efficacy test showed that EEB doses of 200, 400, and 600 mg/kg BW had an anti-diabetic effect on male white rats. The EEB dose of 600 mg/kg is the most effective. Post hoc Tukey test results showed that EEB doses of 200 mg/kg, 400 mg/kg, and 600 mg/kg were not significantly different from the positive control glibenclamide 0.45 mg/kg (p>0.05) and 200,400 ug. and 600 mg/kg BW were significantly different from the negative control CMC Na 0.5% (p<0.05).